2012
DOI: 10.4161/hv.18469
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and long-term persistence of immune response following two doses of an AS03A-adjuvanted H1N1 influenza vaccine in healthy Japanese adults

Abstract: Background Long-term persistence of immune response and safety of two doses of an A/California/07/2009 H1N1 pandemic influenza vaccine adjuvanted with AS03 (an α-tocopherol oil-in-water emulsion-based Adjuvant System) administered 21 d apart was evaluated in Japanese adults [NCT00989612]. Methods One-hundred healthy subjects aged 20−64 y (stratified [1:1] into two age strata 20−40 y and 41−64 y) received 21 d apart, two doses of AS03-adjuvanted 3.75µg haemagglutinin (HA) H1N1 2009 vaccine. Immunogenicity data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
(18 reference statements)
3
5
1
Order By: Relevance
“…This study shows that the 2009 pandemic H1N1 vaccine can induce long-term immunity as assessed by serological assays, which is in line with several previous reports (12)(13)(14). Vaccination is the primary tool for the control of influenza.…”
Section: Discussionsupporting
confidence: 70%
“…This study shows that the 2009 pandemic H1N1 vaccine can induce long-term immunity as assessed by serological assays, which is in line with several previous reports (12)(13)(14). Vaccination is the primary tool for the control of influenza.…”
Section: Discussionsupporting
confidence: 70%
“…Such variation may partly correspond to different biological activities of the antibodies measured by the two methodologies. However, neutralizing seroconversion rates observed in healthy adults receiving two doses of adjuvanted vaccine were as high as 76% at month 6 as compared to 43.2% (54.3% in patients with HAART) in our study [8].…”
Section: Discussioncontrasting
confidence: 69%
“…Virus neutralization by antibodies contained in the serum was determined in a micromethod assay (Viroclinics BV, Rotterdam, The Netherlands) [8]. Sera were tested for the presence in serum of neutralizing antibodies against influenza viruses A/Netherlands/602/2009 pandemic H1N1 influenza virus (a A/California/07/2009-like virus).…”
Section: Laboratory Assaysmentioning
confidence: 99%
“…These formulations elicited very different antigen-specific cytokine/chemokine profiles and patterns of antigen-specific CD4C T cells in re-stimulated splenocytes compared to the HD-unadjuvanted vaccine. Our results confirm the dose-sparing potential of AS03 that has already been demonstrated in the human experience with the AS03-adjuvated pH1N1 vaccine 13,15,16,18,19,24,26 and provide reassurance that this response does not appear to come at the expense of long-term memory. However, there is likely an optimal level of any given antigen (C adjuvant) that will elicit and maintain a multi-faceted immune response.…”
Section: Discussionsupporting
confidence: 78%
“…6,[10][11][12] The pandemic experience created the unusual situation in which much of what we know about the immunological impact of AS03 is derived from human studies. This body of work has demonstrated that AS03-adjuvanted, dose-sparing formulations can induce strong serum antibody responses that persist for at least 12 months in healthy children, [13][14][15][16][17] adults [18][19][20][21][22][23] and the elderly, [24][25][26] and that influenza-specific, poly-functional CD4C T cells can be detected in human PBMC samples for at least 6 months after vaccination. [27][28][29] We have previously shown that AS03 can induce powerful humoral 6,12 and cellular responses 6 to influenza antigens over a surprisingly wide range of Ag doses (100-to 1000-fold lower than a 'standard' 3 mg HA dose in mice) at 3 weeks after a booster immunization The objective of this study was to determine the persistence of these responses up to 34 weeks after LD-AS03-adjuvanted vs. HD-unadjuvanted vaccination.…”
Section: Discussionmentioning
confidence: 99%